Optimizing the agility of badminton athletes through shadow training - Nur Ahmad At Tanzil; Mulyono Mulyono; Santika Rentika Hadi; Nur Hadi (Universitas Sriwijaya, 2025)
Research Problems: Agility is one of the important components in badminton that plays a major role in supporting athlete performance, especially in moving positions quickly and precisely. However, many students who participate in badminton extracurricular activities still experience limitations regarding movement agility. One training method that can be applied to improve agility is shadow training. Research Objectives: This study aims to analyse the effect of shadow training on increasing agility in students who participate in badminton extracurricular activities at Antarika Sidoarjo High School. Methods: The research method used was a one-group pretest-posttest design, where before being given treatment, the sample underwent an initial test (pretest), was then given a shadow training program, and ended with a final test (posttest). The population in this study consisted of 15 badminton extracurricular students, who were also used as research samples. Data collection was carried out through tests and measurements using the agility t-test to assess the level of agility before and after treatment. Results: The results of data analysis conducted with the help of SPSS 23.0 software showed a significant effect of shadow training on improving student agility. This is evidenced by the sig value. (2-tailed) value of 0.003, which is smaller than the significance limit of 0.05. Conclusion: Based on the results of the study, it can be concluded that shadow training contributes positively to improving the agility of badminton extracurricular students at Antartika Sidoarjo High School.